Studying the Effect of the Addition of SiC Molecules as a Nanocomposite on the Optical Properties of a PMMA-PS Blend - Azeez, Hussein Mejbel; Hussein, Marwan Hadi; Abbood, Hussein Abosaooda; Rabee, Bahaa Hussein (Makara Journal of Science, 2025)
In this study, a nanocomposite was prepared using a solution casting technique. The polymer electrolyte blend was formed by combining 0.6 mg of polymethyl methacrylate (PMMA) and 0.4 mg of polystyrene (PS). Subsequently, silicon carbide (SiC) nanoparticles were incorporated into the polymer matrix at varying and precisely measured concentrations. The composite was thoroughly mixed to ensure homogeneity, and Fourier transform infrared spectroscopy spectral analysis confirmed the absence of chemical interactions between the SiC nanoparticles and the polymer components, indicating a physically stable mixture. The above can be reflected in the synthesized compound with new properties, such as semiconductors or semi-insulators. This study aimed to investigate the effect of nanoparticle concentrations on the structure and optical properties of the synthesized samples. To achieve this objective, various techniques were used to characterize the prepared sample, including optical microscopy with a power of 10× and UV-VIS spectroscopy. The absorptivity at the wavelength (200–1100 nm) was also recorded, and the absorption coefficient (a), transmittance (T), real and imaginary dielectric constant (e1 and e2), energy gap of the indirect permissible and forbidden transitions (Eg), extinction coefficient (k0), and refractive index (n) were determined. Based on calculations of previously determined quantities and properties, it was found that the overlap and diffusion of nanoparticles within polymer structures (PS-PMMA) enhanced the optical properties of these nanoparticles as their concentrations increased